Analysis of Settlement Based on Topography in Rabi Jonggor Village, Pasaman Barat RegencY (Sumatra Journal of Disaster, Geography and Geography Education, 2023)
Study this aim analyze spread settlement based on topography in Rabi Jonggor Village , Gunung Tuleh Subistrict, West Pasaman Regency in West Sumatra Province. Analysis is done using secondary data and surveys area. Method Study This with use is qualitative character descriptive , for explain existing phenomenon with give description in a manner clear and appropriate with facts on the ground in detail later served in form map , As for the method data collection, namely primary data and secondary data, which was carried out with method survey right on location research and obtained through Bappeda . As for the results analysis performed is use land in Rabi Jonggor Village, Gunung Tuleh Subdistrict. This consists from Primary forest , shrubs , plantations oil palm , fields, fed rice fields Rain and Settlements . In a number of the year change use land also occurs in the area this. Viewed from spread settlement in Rabi Jonggor Village, Gunung Tuleh Subdistrict. This based on tilt most slopes on slopes Rather steep area of 257.63 ha and settlements on slopes Sloping covering an area of 236.72 ha, with a total area settlements in the area this is 618.88 ha.